Gene Mining and Flavour Metabolism Analyses of Wickerhamomyces anomalus Y-1 Isolated From a Chinese Liquor Fermentation Starter - Shi, Xin; Wang, Xin; Hou, Xiaoge; Tian, Qing; Hui, Ming (Frontiers in Microbiology, 2022)
Luzhou-flavoured liquor is one of China’s most popular distilled liquors. Hundreds of volatile components have been detected from this liquor, with esters as its primary flavouring substance. Among these esters, ethyl hexanoate was the main component. As an essential functional microbe that produces ethyl hexanoate, yeast is an important functional microorganism that produces ethyl hexanoate. The synthesis of ethyl caproate in yeast mainly involves the lipase/esterase synthesis pathway, alcohol transferase pathway, and alcohol dehydrogenase pathway. Wickerhamomyces anomalus is one of the main functional yeasts that produce ethyl hexanoate, but the mechanism of its production is unclear. In this study, whole genome sequencing of W. anomalus Y-1 isolated from Songhe medium-temperature Daqu, a fermented wheat starter containing brewing microorganisms, was carried out using the Illumina HiSeq X Ten platform. The sequence had a length of 15,127,803 bp with 34.56% GC content, encoding 7024 CDS sequences, 69 tRNAs, and 1 rRNA. Then, genome annotation was performed using three high-quality databases, namely, COG, KEGG, and GO databases. The annotation results showed that the K07019 pathway of gene 6340 contained the Eht1p enzyme, which was considered a putative acyltransferase similar to Eeb1p and had 51.57% homology with two known medium-chain fatty acid ethyl ester synthases, namely, Eht1 and Eeb1. Ethyl hexanoate in W. anomalus was found to be synthesised through the alcohol acyltransferase pathway, whilst acyl-coenzyme A and alcohol were synthesised under the catalytic action of Eht1p. This study provides a reference for further study on the synthesis of ethyl hexanoate and the improvement of Luzhou-flavoured liquor.